The Influence of Rock Resistance for Geomorphology of Krakatau Islands, South Lampung District, Lampung Province. Issue 1 (November 2020) - Ismail, Taufik; Abdurrachman, Mirzam; Rizal, Yan; Hardjawidjaksana, Kumala; Arbie, Rahmawati
Abstract: Krakatoa Islands is one of the results of high activity volcanic islands located in the Sunda Strait, Indonesia. Volcanic activity of the research area is highly influential on the typical morphological conditions. Rocks produced from this volcano activity a role in the formation of geomorphology that is typical of areas with high volcanic activity. Rocks in the study area were the result of volcanic activity such as lava, pyroclastic alluvial. Geomorphology analysis was conducted by analyzing river flow pattern, slope criteria analysis and shoreline analysis since 1984. East Anak Krakatoa island which is dominated by lava, in contrast to the krakatoa west of which the rock formers are dominantly pyroclastic fall. Unconsolidated rocks form west Sertung island, east Panjang island and south Rakata island which the rock formers are dominantly pyroclastic flow. Evidence of 1883 catastrophic eruption is highly visible on the north Rakata island, east Sertung island and west Panjang island shown by vertical high cliff which is indicated as a caldera structure. The results of the geomorphological analysis are poured into geomorphological maps. Geomorphology unit in research area consist of 9 (nine) geomorphology units of Krakatoa Islands. Krakatoa Islands in this geomorphological case, is still controlled by climate change, erosional of sea water wave, 1883 catastrophic eruption which produces rock in the form of lava and pyroclastic and volcanic activity still continues to this day.